Validity of the "fall back" test for boldness - Veličković, Saša (Revija za elementarno izobraževanje, 2016)
Synonyms for the word boldness include courage, fearlessness, heroism and bravery. The best examples of courage in sport are athletes who, despite difficult situations, conditions and strong competition, perform very risky elements, break records, etc. The "Fall back" measurement instrument has been used in the selection process for artistic gymnastics. Bearing in mind that this test requires a drop back down an inclined plane, it requires a degree of courage in the realization of this motor task. The aim of this research is to determine the validity of the "fall back" test and to answer the question: Is the "Fall back" test actually a measure of courage among beginners in the sport? In this study, the research sample consisted of 16 boys and 33 girls, third graders from the Jovan Cvijic elementary school in Kostolac, aged nine years (+/- 6 months). The sample of variables represented the results written using two measurement instruments: 1. Psychological survey -test of boldness and courage - PSBC (a test modeled after the - Erikson`s theory of Psyhosocial Development test - About.com Psyhology); 2. Situational motor measuring instrument - Fall back - MFIB. The resulting measurements were analyzed by the appropriate statistical methods, which are congruent with the set objective and task ofthe study. The validity of the "Fall back" situational-motor test is determined by calculating the coefficient of correlation (r) between said composite test and a psychological test of courage. The very high coefficients of correlation that resulted in all three cases (total sample r = .846, sample of boys r = .873, a sample of girls r = .845) indicate a high validity level for the test, "Fall back", that is, the subject of measurement in the test, largely corresponds with the subject of measurement in the PSBC psychological test. The height of the correlation coefficient also justifies the use of the "Fall back" test as a composite test. A high validity of the "Fall back" measurement instrument (MFIB), which is indicated by the high Pearson coefficients of correlation between the"Fall back" measurement instruments and the psychological test of courage and boldness, was established for all three samples of respondents.
Keywords: boldness; sport; šport; športniki; tests; drznost; fall back; pogum; validity